Continuous Delivery Sounds Great, but Will It Work Here? - HUMBLE, JEZ (Communications of the ACM, 2018)
The article discusses the implementation of continuous delivery in software deployment and development. Topics include risk-mitigation strategies used by businesses that implement continuous delivery, the role of continuous delivery in the LaserJet Firmware division of the firm Hewlett-Packard Co., and the use of continuous delivery by the firm Suncorp Group Ltd.